The Wind in the Rose-Bush, and Other Stories of the Supernatural - Freeman, Mary Eleanor Wilkins, 1852-1930 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Wind in the Rose-Bush, and Other Stories of the Supernatural" by Mary Wilkins is a collection of supernatural short stories likely written in the late 19th century. The themes center around eerie experiences, often highlighting the struggles and complexities of human emotions, set against a backdrop of uncanny events. The opening story introduces Rebecca Flint, a pale and reserved spinster who travels to Ford Village to reclaim her niece, Agnes, but soon encounters a sense of foreboding surrounding her sister-in-law, Mrs. Dent, and the unsettling atmosphere of the house. At the start of the collection, Rebecca arrives in a small village, managing an uncomfortable interaction with curious townsfolk during a ferry ride. As she comes closer to her destination and learns about her niece, the chilling interactions with Mrs. Dent hint at suspicious undertones and perhaps deeper mysteries at play. The peculiar reactions of the townsfolk, especially when Rebecca mentions her sister-in-law, suggest that there might be secrets lurking beneath the surface. The arrival of Rebecca sets in motion a series of unnerving events, foreshadowing the supernatural occurrences that will unfold in her quest to reunite with Agnes, while her own emotional state becomes intertwined with the haunting environment she steps into. (This is an automatically generated summary.)
The wind in the rose bush -- The shadows on the wall -- Luella Miller -- The southwest chamber -- The vacant lot -- The lost ghost.
Release date is 1999-01-01
Produced by Donald Lainson. HTML version by Al Haines.
Keywords: Short stories, American; Ghost stories, American; New England -- Fiction; Paranormal fiction, American